Pop-Up Book to Improve Reading Skills in Indonesian Language Learning at Madrasah Ibtidaiyah - Alvin Yanuar Rahman; Nun Asmi Aida; Asis Saefuddin; Siti Khozanatu Rohmah; Sani Insan Muhamadi (Universitas Islam Negeri (UIN) Salatiga, 2025)
Objectives: This study aims to determine the effectiveness of Pop-up book learning media in improving students’ reading comprehension skills in Indonesian language subjects. Method: This research employs a quantitative method with a one group pretest posttest design. The procedure involves administering a pretest, applying the Pop-up book learning media, and conducting a posttest. The population consists of students at MI Bahrul Ihsan, Indonesia with a sample of 20 students selected using purposive sampling. Data were collected using test instruments in the form of reading comprehension questions. Data analysis includes the normality test, paired t-test, and N-Gain formula. Results: The research concludes that the use of Pop-up book learning media is effective in improving the reading comprehension skills, and an N-Gain score of 0.67 in the medium category with 66.67% effectiveness, classified as quite effective. Theoretical Contribution: This study supports the concept of holistic development in Islamic education (tarbiyah) by emphasizing active student engagement, reflection (tafakkur), and deep understanding (tafaqquh). The media encourages intellectual growth (‘aql) aligning with the goals of ta’līm (instruction) and purification (tazkiyah). Implication: Improving reading skills in Indonesian Language can use pop-up book learning media. Future research should involve a larger and more diverse sample.